The combination of nanoparticles and endophytes boosts Thyme (Thymus vulgaris L.) resistance to drought stress by elevating levels of phenolic compounds, flavonoids, and essential oils - Afsoun Kamyab; Davood Samsampour; Navid Ahmadinasab; Abdonnabi Bagheri (Chemical and Biological Technologies in Agriculture)
Abstract Background As climate change and water scarcity increasingly threaten agricultural productivity, enhancing plant resilience to drought has attracted great attention. This study explored the potential of combining Fe2O3 nanoparticles (FeNPs), endophytic bacteria (EB), and endophytic fungi (EF) to boost drought tolerance in Thymus vulgaris. The research aimed to assess how these combined treatments affect the plant’s physiological responses and chemical composition under drought stress. Results A factorial experiment was designed using completely randomized design (CRD) method, incorporating four irrigation levels [100%, 75%, 50%, and 25% field capacity (FC)], four FeNPs concentrations (0, 0.5, 1, and 1.5 mg L−1), and three endophyte types (control, bacteria, and fungi). After extracting, purifying, identifying, and screening EB and EF from nine Lamiaceae species, the endophytes Azospirillum lipoferum and Aspergillus oryzae isolated from Salvia mirzayanii exhibited the highest drought resistance. The highest amounts of TFM (45.45 g) and TDM (21.56 g) were obtained using the combination of EB and FeNPs at 1 mg L−1 under irrigation with 100% FC. At 25% FC, EB treatment increased the activities of polyphenol oxidase (PPO) and phenylalanine ammonia-lyase (PAL) by 62.12% and 18.23% compared to the control, respectively. In addition, under optimal humidity conditions, FeNP concentrations were higher than 0.5 mg L−1 leading to a decrease in PPO activity. At 25% FC, the highest content of total phenols was observed with a 37.5% increase under EB treatment using 1 mg L−1 of FeNPs, while the highest content of total flavonoids showed a 62.72% increase under EF treatment with 0.5 mg/L of FeNPs. The highest level of p-coumaric acid was obtained under EF (34.27% compared to control). At 25% FC, EB and FeNPs (1 mg L−1) increased the level of caffeic acid in thyme plants by 24.70% and 10.08%, respectively. In addition, inoculation with EB increased (11.9%) the content of ferulic acid in plants and the application of FeNPs as a foliar spray decreased the level of ferulic acid in thyme plants. The highest essential oil percentage at 25% FC was observed after inoculation with EF and FeNPs (0.5 mg L−1), resulting in significant increases of 14.7% and 82.12%, respectively, compared to the control. A decrease in irrigation level led to an increase in the percentage of essential oil in thyme plants while decreasing dominant essential oil compounds, thymol, and carvacrol. The levels of thymol and carvacrol in the essential oil were not affected by the interaction effects of drought stress, endophytes, and FeNPs. EF and FeNPs (1.5 mg L−1), respectively, caused significant increases of 17.44% and 29.87% compared to the control in the amount of thymol and significant increases of 13.75% and 31.01% in the amount of carvacrol. All FeNPs concentrations decreased the concentrations of ferulic acid, FeNPs (1.5 mg L−1) and PPO; these particles act as abiotic stressors at sub-toxic levels and become phytotoxic at higher concentrations. Conclusions It seems that combining endophytes with FeNPs showed promise in enhancing drought tolerance in T. vulgaris. These treatments have significantly contributed to the production of enzymatic antioxidants, flavonoids, and phenolic compounds, leading to a reduction in the amounts of oxidants. At the same time, they have improved both the quality and quantity of essential oils. This highlights the importance of establishing an effective antioxidant system in response to environmental stresses. Graphical Abstract